Pentingnya Bimbingan Karier di Sekolah - Ardiansyah, Andika Tri; Octavia, Putri Neva; Asbi, Asbi (Universitas Muhammadiyah Enrekang, 2024)
Career guidance at school has a very important role in helping students prepare themselves to enter the dynamic and competitive world of work. This article examines the importance of career guidance by reviewing various literature, implementation methods, research results, and challenges faced. Through this research, it was found that career guidance not only helps in choosing the right educational and career path, but also develops important life skills that support students' long-term success. This article emphasizes the need for collaboration between schools, families, and industry to create effective and sustainable career guidance programs.